Income Contribution of Housewives Selling Typical Souvenirs of the Luwu Region to Family Income in Baramamase Village Walenrang District Luwu Regency - Jumriah Jumriah (UNM Geographic Journal, 2020)
This study aims to determine: 1) how much the income contribution of housewives selling typical Luwu souvenirs to family income, 2) what are the driving and inhibiting factors of housewives selling typical Luwu souvenirs to family income, 3) how double workload faced by housewives selling souvenirs typical of the Luwu region in increasing family income. The population in this study are all housewives who sell souvenirs typical of the Luwu region with a total sampling research method that is descriptive qualitative and quantitative. The results showed that: 1) The income contribution of housewives selling souvenirs typical of the Luwu region to family income was 85%. This shows that the income contribution given by housewives in their families is quite large. 2) Factors that support the smooth business of selling souvenirs typical of the Luwu area, namely because of its location on the side of the cross-city / district axis road which makes it easy for buyers to stop while the inhibiting factor for the efforts of these housewives in running their business is the stopover location / narrow parking lot. , the high cost of raw materials (brown sugar) and the lack of capital to develop their business. 3) With the participation of housewives working in the public sector, of course, housewives also do not leave their duties in the domestic sphere, namely housework.